HODOWLA BYDŁA W STAROŻYTNYM RZYMIE - Kuszewska, Katarzyna (Collectanea Philologica, 2013)
The Romans believed that they originated from shepherds, and that the profession of a farmerwas considered a noble occupation. In both agriculture and pastoralism the crucial role playedcattle. Thanks to a very well-preserved agronomic Latin literature, we can accurately describe thecultures of these animals in ancient Rome. The most important sources of knowledge are Cato theElder, Varro, Columella and Palladius. Farming description contains the information of theoptimal age, race and appearance of the animal on which you need to pay attention when buyingcattle. It also describes the most appropriate living conditions on the farm, such as animal housing,nutrition, health as well as breeding (the best age to breed, length of pregnancy, care of younganimals and castration). Moreover, it provides valuable knowledge about most common diseasesand their treatment and the benefits of keeping the animal. The description presented in an ancientliterature nowadays allows the building of a big picture on the issue of breeding and keeping cattle.